2022
DOI: 10.12965/jer.2244146.073
|View full text |Cite
|
Sign up to set email alerts
|

A brief descriptive outline of the rules of mixed martial arts and concussion in mixed martial arts

Abstract: Mixed martial arts (MMA), a combat sport consisting of wrestling, box-ing, and martial arts, is a popular activity associated with danger and vi-olence. Of concern are the repetitive head impacts, both subconcussive and concussive, sustained by MMA athletes. The rules of MMA en-courage head strikes, but there was no formal concussion protocol in the Ultimate Fighting Championship (UFC) until 2021. Because the UFC was established less than 30 years, the long-term consequences of these repetitive concussive head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
1
2
0
1
Order By: Relevance
“…Furthermore, this was confirmed by recent studies on the dimensions of aggression among athletes practicing martial arts and combat sports [41]. The range of MMA rules also includes many brutal techniques, i.e., front kicks to the thigh, heel kicks to the feet, elbow strikes, and multiple knee kicks while holding the head [32].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, this was confirmed by recent studies on the dimensions of aggression among athletes practicing martial arts and combat sports [41]. The range of MMA rules also includes many brutal techniques, i.e., front kicks to the thigh, heel kicks to the feet, elbow strikes, and multiple knee kicks while holding the head [32].…”
Section: Discussionsupporting
confidence: 54%
“…What seems to be important is the structure of the entire fight, which consists of stand-up and ground fighting, in which the athlete can perform elbow strikes, hammer punches, and kicks on a lying opponent [32]. This is particularly significant in the context of reports by Kalu żny and Kalina [33], who proved that the most common response of an aggressively attacked man is an even greater level of aggression toward the attacker.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-specific biomarkers for use as diagnostic tools in brain injury have become more prevalent in recent years. Research on NfL chain peptides as potential biomarkers for axonal injury has been observed in certain contact sports studies since it is the most abundant neurofilament, with increased levels 24–48 h following concussion [ 97 , 98 ]. None of our athletes experienced a concussion which may explain why we do not see differences in any of the tested biomarker protein concentrations following all contact sessions.…”
Section: Discussionmentioning
confidence: 99%
“…O principal evento do MMA atualmente é o Ultimate fighting championship (UFC), neste evento os lutadores são separados em categorias de acordo com o peso, que deve ser batido no dia anterior a luta (dia da pesagem oficial), entre as categorias temos: Peso-palha (Feminino, até 52,1 Kg), peso-mosca (Masculino e feminino, até 56,7Kg), peso-galo (Masculino e feminino, até 61,2Kg), peso-pena (Masculino e feminino, até 65,7Kg), peso-leve (Masculino, até 70,3Kg), peso meio-médio (Masculino até 77,1Kg), peso-médio (Masculino até 83,9Kg), peso meio-pesado (Masculio, até 92,9Kg) e peso pesado (até 120,2 Kg). No UFC não há restrição para perda de peso nos atletas (Hamdan et al, 2022).…”
Section: Artes Marciaisunclassified